A Scientometric Visualization Analysis for Molecular Mechanisms of Substance Abuse and Its Neurotoxicity From 1997 to 2021 - Zhang, Aijia; Liu, Zilong; Liang, Man (Frontiers in Molecular Neuroscience, 2022)
Substance abuse has become a global problem due to drug-induced addiction and neurotoxicity, which causes a huge physical, social and financial burden. Various kinds of drugs can hijack the users’/abusers’ behavior and associated neurocircuitry. In order to summarize recent scientific advances on drug abuse, we reviewed relevant publications to analyze research progress and such trends through bibliometric ways. Based on retrieval strategies, a total of 681 scientific records published from 1997 to 2021 were screened and included from the Web of Science (WoS) database. Further scientometric analysis revealed annual publication output increased across this period, with the United States of America (USA) contributing a significant number of reasons. Research has focused on neurotransmitter, oxidative stress, mitochondrial system injury and other neurotoxic mechanisms. Neuroimmune, neurotoxic targets, and new psychoactive substances have been hot topics in recent years, which deserve continued research in the future. Specific research on molecular mechanisms have progressed across this period, with an emphasis on the root-cause of toxicity and molecular targets for therapy. Moreover, collaborations of international multi-disciplinary research teams have been efficient and need to be encouraged on addiction research and developing appropriate therapeutic processes.